2015
DOI: 10.2134/cftm2014.0097
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of Shallow Subsurface Drip Irrigation Tubing under Three Tillage Practices

Abstract: Shallow Sub‐Surface drip irrigation (S3DI) has drip tubing buried about 2 inches below the soil surface. It is unknown how long drip tubing would be viable at this shallow soil depth using strip‐ or no‐tillage systems. The objectives were to determine drip tube longevity, resultant crop yield, and partial net revenue when using conventional, strip‐, and no‐tillage. Drip tubing (8, 10, and 15 mil) was buried 1.5 inches in 2006 and left in the field for five years under strip‐ and no‐till areas and removed and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The use of S3DI in field crops is easily installed and economical (Sorensen and Lamb, 2008; Sorensen and Lamb, 2009; and Sorensen and Lamb, 2015). Drip tubing was left in the field for five years with a cotton–corn–corn–corn–peanut rotation.…”
Section: Useful Conversionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of S3DI in field crops is easily installed and economical (Sorensen and Lamb, 2008; Sorensen and Lamb, 2009; and Sorensen and Lamb, 2015). Drip tubing was left in the field for five years with a cotton–corn–corn–corn–peanut rotation.…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Thinner wall tubing (8 mm) had 3.5 times more holes compared with thicker wall tubing (15 mm). The “cost‐to‐repair” versus “cost‐to‐replace” tubing indicates average replacement time at about 5.4 years (Sorensen and Lamb, 2015). Both corn and cotton have open‐type canopies such that rodents cannot hide from predators quite as easily as compared with a closed canopy structure such as peanut.…”
Section: Useful Conversionsmentioning
confidence: 99%
“…There were seven tiers orientated perpendicular to individual plot rotations (Figure 1; Balkcom et al., 2001; Lamb et al., 2010, 2011, 2015). Tiers 1, 2, and 3 were established for an SSDI system.…”
Section: Site Location and Plot Designmentioning
confidence: 99%
“…The alternate row middle lateral spacing would be less expensive to install by using less drip tubing while having the same yield. Both Sorensen et al (2011) and Sorensen and Lamb (2015) showed that drip tubing placed under individual crop rows did not increase yield in cotton and peanut, respectively. The S3DI irrigated cotton had greater yield than SSDI irrigated cotton at the 100% irrigation level.…”
Section: Shallow Subsurface Drip Irrigation Versus Subsurface Drip Irmentioning
confidence: 99%
See 1 more Smart Citation